Non-invasive stereotactic ablative boost in patients with locally advanced cervical cancer. Issue 11 (November 2020) - Dalwadi, Shraddha; Echeverria, Alfredo; Jhaveri, Pavan; Bui, Tung; Waheed, Nabila; Tran, Danny; Bonnen, Mark; Ludwig, Michelle
Abstract : Introduction: The current literature is insufficient to guide care for patients with cervical cancer ineligible for brachytherapy. Stereotactic ablative radiotherapy boost is a clinical necessity for these patients, but highly debated among radiation oncologists. Objective: To report toxicity and survival outcomes in a large cohort of patients with locally advanced cervical cancer treated with a non-invasive stereotactic ablative radiotherapy boost instead of brachytherapy Methods: Patients with locally advanced cervical cancer were entered, between January 2008 and December 2018, who were recommended definitive intent external boost after pelvic radiotherapy to 45–50.4 Gy concurrent with weekly cisplatin and simultaneous/sequential nodal boost up to 55–66 Gy. Simulation CT was facilitated using radio-opaque fiducials, empty rectum, dedicated bladder filling, and whole body vaculoplastic immobilization. Kaplan-Meier survival estimates were used to report local/regional recurrences, distant metastases, cancer-specific survival, and overall survival. Results: A total of 25 patients were analyzed. Median follow-up was 25 months (range 6–54). Patients received stereotactic ablative radiotherapy due to refusal of brachytherapy (9/25, 36%), medical co-morbidities limiting implantation (9/25, 36%), or technical infeasibility (7/25, 28%). Typical fractionation was 24–30 Gy in 4–5 fractions (24/25, 96%). The most common long-term toxicity was grade 1–2 vaginal dryness, discomfort, stenosis, and/or dyspareunia (4/25, 16%). One patient had new post-treatment grade 4 fistula in an area of previous tumor erosion (1/25, 4%). Overall survival, cancer specific survival, loco-regional control, and distant control were 95.5%, 100%, 95.5%, and 89.1%, respectively, at 2 years. Conclusion: Further study of stereotactic ablative radiotherapy boost for cervical cancer is needed; a brachytherapy-similar approach portends clinical success with 95.5% overall survival and loco-regional control at 2 years.